2022
DOI: 10.3390/ijerph19116918
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Motivation Systems, Anxiety, and Low Self-Control in Smartphone Addiction among Smartphone-Based Social Networking Service (SNS) Users

Abstract: Given that Social Networking Service (SNS) has emerged as the most influential platform, which can lead users to addictive smartphone use, it is necessary to investigate which psychological variables lead smartphone-based SNS users to addictive smartphone use. Still, studies on the relationship between psychological variables and addictive smartphone use among smartphone-based SNS users remain to be explored. Therefore, this study aims to investigate the role of psychological factors on smartphone addiction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…For the mediating role of social support, the likely reason is that support from family, teachers, and friends is used as a resource to perform self-control, and which is prior studies that indicated a positive relationship between a low level of self-control and MPD. 75 Learning burnout is considered to be a negative emotion that depletes adolescents’ limited resources and gradually negatively affects self-control. 76 Many off-campus education institutions have disappeared or are on the verge of closure as the “double reduction” policy has been effectively implemented for more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…For the mediating role of social support, the likely reason is that support from family, teachers, and friends is used as a resource to perform self-control, and which is prior studies that indicated a positive relationship between a low level of self-control and MPD. 75 Learning burnout is considered to be a negative emotion that depletes adolescents’ limited resources and gradually negatively affects self-control. 76 Many off-campus education institutions have disappeared or are on the verge of closure as the “double reduction” policy has been effectively implemented for more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in keeping with the conclusion drawn from previous studies that found that individuals with increased anxiety symptoms have an increased risk of smartphone addiction ( 6 , 15 , 43 ). A possible explanation is that people with anxiety tend to experience feeling of powerlessness and helplessness, and have a fear of being isolated from or even ostracised by the social communities ( 17 , 44 ). This might lead them to repeatedly use a smartphone to be connected with others and alleviate this anxiety ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] studied the detection of depression using AI. In addition, studies [ 8 , 9 , 26 , 27 ] studied depression and anxiety. Additionally, ref.…”
Section: Literature Review: Anxiety and Depression In Snmentioning
confidence: 99%
“…In [ 18 ], the research studied depression symptoms among users of WeChat in China. The study concluded “that using social media WeChat showed an association with lower depressive symptoms among people aged ≥45 and older in the study sample.” In [ 27 ], the research investigated the role of psychological factors on smartphone addiction proneness (SAP), namely anxiety and low self-control in Korea. In [ 24 ], the research studied depression and anxiety symptoms in users of smartphone SN.…”
Section: Literature Review: Anxiety and Depression In Snmentioning
confidence: 99%